Eficácia dos ácidos orgânicos comerciais no desempenho de frangos de corte desafiados com micotoxinas - Schavetock, Bruno Ruberto (2022)
The use of organic acids in poultry nutrition is important due to its ability to regulate the intestine, suppressing pathogenic bacteria and improving the intestinal barrier, and may be used as a replacement for growth-promoting antibiotics. The aim of this study was to evaluate the effects of commercial products composed of organic acids, used in the diets and drinking water of chickens challenged with mycotoxins. A total of 1296 male Cobb 500® broilers that had their productive performance evaluated from 1 to 42 days of age were used. The animals were randomly arranged in 6 treatments with 8 replicates of 27 animals each, totaling 216 birds per treatment. All groups received a basal diet, with the T1 group being fed only the basal diet, in the T2 group, 0.15 mg/kg of aflatoxins (Afla), 50 mg/kg of fumonisins (Fumo) and 25 mg/kg were added to the diet. kg of deoxynivalenol (Don). In groups T3 to T6, mycotoxins from group T2 and three commercial products called products A, B and C were added. Product A (phenolic compound, butyrates and medium chain fatty acids) in the following manner: 1.5 kg/t (initial phase), 1 kg/t (growth phase) and 0.5 kg/t (final phase), product B (composed of smectite clay minerals, glucose biopolymer and β-glucans) was added 1.5 kg/t in the ration and the product C (composed of a combination of acetic acid and formic acid) was diluted in the drinking water at a concentration of 1 liter per m³ of water. In group T3, product B was added; in group T4, products A, B and C, in group T5, products A and B and in group T6, products B and C. The performance parameters used were: weight gain, feed conversion, feed intake and daily weight gain. The results indicated that the inclusion of afla, fumo and don mycotoxins with or without treatment did not significantly influence feed intake or feed conversion during the experimental period. However, the impact observed in the other productivity indicators (weight gain and daily weight gain) showed an asymptomatic condition, improving these indicators when compared to treatment 2 containing only mycotoxins.